The Impact of Junk Food on Children's Health and Development - Bhandari, Bhuwan (Rupantaran: A Multidisciplinary Journal, 2025)
The present study investigates the impact of junk food consumption on the health and development of school students in Dhankuta Municipality. Junk food, is the term used to describe food that has empty calories and provides little or no nutritional value to both children and adults, it is associating with the increasing trends among children globally as a result of urbanization, globalization and aggressive advertising during childhood (Vrushali, D. and Seema, S. 2021). This study is a cross-sectional and descriptive analytical study using semi-structured questionnaires, which are distributed to students, parents & educational experts. The aims of the research are to determine junk food habits in children and frequency, effect of junk food on physical health as well as behavioral patterns, and influences over children's food consumption like advertisement advertisements, peer pressure or convenience. The Outcome shows that 70 percent of kids eat junk meals minimum 2-three instances in a week, and speedy meals, sweet beverages are the maximum usual types of meals eaten. Some of the health effects reported include weight gain (40 %), low energy (25 %), and stomach problems (15 %). Besides, intake of junk food leads to changes in behavior such as increased excessed and decreased attention at school. Advertising (40%), peer pressure (30%) and convenience (25%) are the factors of influencing. Well-documented evidence of a causal chain between school feeding and child outcome stresses the importance of school-focused health education programming that encourages children to eat better while decreasing junk food intake. These prevention strategies are critical to reducing the risk of cardiovascular disease in children.